Differences in Preferences Towards the Environment: The Impact of a Gender, Age and Parental Effect - Benno Torgler; María A. García-Vali\~nas; Alison Macintyre (Center for Research in Economics, Management and the Arts (CREMA), 2007)
The paper investigates empirically the differences in preferences towards protection of the environment. Using seven different dependent variables to focus on the impact of age, gender and children we use a large micro data set covering data from 33 Western and Eastern European countries. The results indicate that women have both a stronger preference towards the environment and a stronger willingness to contribute. Moreover, we observe the tendency of a negative correlation between age and environmental preferences. However, a positive effect is visible once we focus on the impact of age on social norms (environmental morale). Finally, we were not able to observe that having children is positively correlated with a stronger preference towards the environment.
Keywords: H26; H73; D64; 330; environmental preferences; environmental morale; gender; age; children